PENINGKATAN PEMAHAMAN SISWA MELALUI METODE MIND MAPPING PADA MATERI KEEMASAN ISLAM ERA DAULAH ABBASIYAH - Bella Ferlyna; Muhammad Bagus Kurniawan; Muhammad Ali Rohmad (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT The mind mapping method is a learning method that makes it easier for students to understand lesson material imaginatively through the presentation of ideas or concepts that are simple, structured, and easy to understand. The application of this method in learning Islamic Cultural History, particularly material about the Islamic Golden Age during the Abbasid Caliphate, is estimated to enhance students' understanding of the lesson material. The purpose of this study is to determine whether the mind mapping technique improves students' understanding of Islamic Cultural History. The aim of this research is to find out how well the mind mapping technique improves students' understanding of Islamic Cultural History. Purposive sampling and quantitative methodology are used in this study. As research instruments, pre-tests and post-tests are used to measure students' understanding both before and after the learning strategy is applied. The research data is examined to observing how the mind mapping approach affects student learning outcomes. According to the analysis findings, students' understanding of the Golden Age of Islam during the Abbasid Era increased by 46.66 points when the mind mapping technique was applied. In addition, learning became more dynamic and supported students in understanding the relationships between ideas more systematically. Thus, it has been proven that the mind mapping approach significantly improves students' understanding of Islamic Cultural History. ABSTRAK Metode mind mapping merupakan metode pembelajaran yang memudahkan siswa memahami materi pelajaran secara imajinatif melalui penyajian ide maupun konsep yang sederhana, terstruktur, dan mudah dipahami. Penerapan metode ini dalam pembelajaran Sejarah Kebudayaan Islam, khususnya materi tentang Masa Kejayaan Islam pada masa Kekhalifahan Abbasiyah, Diperkirakan bahwa hal ini akan meningkatkan pemahaman siswa terhadap materi pelajaran. Tujuan dari penelitian ini adalah untuk menentukan apakah teknik mind mapping meningkatkan pemahaman siswa terhadap Sejarah Kebudayaan Islam. Tujuan dari penelitian ini adalah untuk mengetahui seberapa baik teknik mind mapping meningkatkan pemahaman siswa terhadap Sejarah Kebudayaan Islam. Pengambilan sampel purposif dan metodologi kuantitatif digunakan dalam penelitian ini. Sebagai instrumen penelitian, pre-test dan post-test digunakan untuk mengukur pemahaman siswa baik sebelum maupun sesudah strategi pembelajaran diterapkan. Data penelitian diperiksa untuk melihat bagaimana pendekatan mind mapping memengaruhi hasil belajar siswa. Menurut temuan analisis, pemahaman siswa tentang Masa Keemasan Islam pada Era Abbasiyah meningkat sebesar 46,66 poin ketika teknik mind mapping diterapkan. Selain itu, pembelajaran menjadi lebih dinamis dan mendukung siswa dalam mengetahui hubungan antar ide dengan lebih sistematis. Dengan demikian, telah dibuktikan bahwa pendekatan mind mapping secara signifikan meningkatkan pemahaman siswa tentang Sejarah Kebudayaan Islam.